Synthesis and applications of large-area single-layer graphene. Issue 22 (12th February 2016) - Lin, Xiao-Hong; Gai, Jing-Gang
Abstract : The progresses in syntheses of large-area single-layer graphene and applications in membrane separation are summarized in this review. Abstract : Large-area graphene is gaining heightened attention in the fields of optoelectronics and highly selective membrane separation due to its unique physicochemical properties including exceptionally high surface, electro mobility, thermal conductivity, mechanical strength, and one atom thickness. These outstanding properties can lead to novel or improved technologies to address the pressing global challenges in transparent conducting electrodes, transistors, ultrathin electromagnetic shielding film, osmotic energy production, highly selective single molecule gas detection, desalination, DNA sequencing, etc. This review assesses the progress in two categories of methods for preparing large-area graphene, namely chemical assembly of small graphene sheets and chemical vapor deposition method. We also discuss the challenges for preparing large-area graphene with high qualities and controllable layers and for transferring graphene film to various substrates with large area, clean, and low defect surface. Applications of large-area graphene in the optoelectronics fields have been discussed by Bonaccorso et al. We mainly discuss its applications in highly selective membrane separation including single molecule gas detection, desalination, DNA sequencing and osmotic energy production. Finally, we outline the global investment and industrial production of large-area graphene.